Penggunaan Istilah Asing (Gairaigo) Daily Life dalam Kanal Youtube Crazy Magnet (Kureiji Magunetto): Kajian Morfologi - Wiyatasari, Reny; Rahman, Aufa (Faculty of Humanities, Diponegoro University, 2025)
Language change is a dynamic phenomenon that evolves along with societal development. One contributing factor is technological advancement, which facilitates interaction between communities and individuals with diverse linguistic backgrounds. This interaction can lead to new understandings within a language, ultimately driving language changes. One form of language change in Japanese is gairaigo, or loanwords from foreign languages adapted to suit speakers’ communicative needs. This study aimed to expand the discussion on the morphological forms of gairaigo, particularly in the context of daily life usage in digital media. A qualitative descriptive method was employed, using a video from the CrazyMagnet YouTube channel titled 「仲良し3姉妹がチート爆食い中になぜか動物の森迷い込んで癒されすぎてヤバい」 (Nakayoshi 3 shimai ga chiito baku kui naka ni nazeka Doubutsu no Mori mayoikonde iyasare sugite yabai) as the data source. The analysis identified 18 instances of gairaigo in the video. Three types of morphological processes were identified: compounding (4 cases), clipping (2 cases), and borrowing (12 cases). The results indicate that gairaigo in digital media functions not only as a lexical supplement, but also as a marker of linguistic style and cultural identity among Japanese youth. This study emphasizes the role of gairaigo in ongoing linguistic dynamics, particularly in relation to digital platforms, such as YouTube, which are integral to popular culture. While previous studies have often focused on thematic contexts, such as beauty or cuisines, the use of gairaigo in everyday contexts remains underexplored. This study seeks to address this gap by providing insights into the morphological characteristics of gairaigo in daily life content on YouTube